Generic Synopsis of the Formicidae of Vietnam (Insecta: Hymenoptera), Part I — Myrmicinae and Pseudomyrmecinae - Eguchi, Katsuyuki; Viet, Bui Tuan; Yamane, Seiki (Zootaxa, 2011)
Alpha taxonomy of Vietnamese ants was initiated by European and American authors in the early 20th century, and approximately 160 species and infraspecific taxa were described or recorded in this early period. From 1965 to 1966 an inventory project of insects in northern Vietnam was conducted by the Agriculture Ministry of Vietnam, and 36 ant species were recorded. The identity of those taxa, however, needs to be revised based on the modern taxonomy of ants. Since theend of the 1980's dozens of ant species have been newly recorded or described from Vietnam. Regional revisions dealing with Vietnamese species have also been published for several genera including Myrmica, Probolomyrmex, Pheidole, Acanthomyrmex and Anillomyrma. Furthermore, two new genera, Parvimyrma (Myrmicinae) and Opamyrma (Amblyoponinae), were recently described from the country. However, there has been no comprehensive systematic treatment of the Vietnamese ants to date. In order to develop the taxonomy of ants in Vietnam, we have begun a program to: (1) explore local ant faunas; (2) give species codes to all species; (3) overview ant genera known from Vietnam; (4) describe unnamed taxa and review higher taxa known from Vietnam and adjacent areas. Ninety-two genera in twelve subfamilies have so far been recognized by us: DOLICHODERINAE: Chronoxenus, Dolichoderus, Iridomyrmex, Liometopum, Ochetellus, Philidris, Tapinoma, Technomyrmex; FORMICINAE: Acropyga, Anoplolepis, Camponotus, Cladomyrma, Echinopla, Gesomyrmex, Lasius, Lepisiota, Myrmoteras, Nylanderia, Oecophylla, Paratrechina, Paraparatrechina, Plagiolepis, Polyrhachis, Prenolepis, Pseudolasius, Undescribed genus "eg-2"; PSEUDOMYRMECINAE: Tetraponera; CERAPACHYINAE: Cerapachys, Simopone; AENICTINAE: Aenictus; DORYLINAE: Dorylus; LEPTANILLINAE: Leptanilla, Protanilla; AMBLYOPONINAE: Amblyopone, Myopopone, Mystrium, Opamyrma, Prionopelta; PONERINAE: Anochetus, Centromyrmex, Cryptopone, Diacamma, Harpegnathos, Hypoponera, Leptogenys, Odontomachus, Odontoponera, Pachycondyla, Platythyrea, Ponera; ECTATOMMINAE: Gnamptogenys; PROCERATIINAE: Discothyrea, Probolomyrmex, Proceratium; MYRMICINAE: Acanthomyrmex, Anillomyrma, Aphaenogaster, Calyptomyrmex, Cardiocondyla, Cataulacus, Crematogaster, Dacatria, Dilobocondyla, Gauromyrmex, Kartidris, Lasiomyrma, Liomyrmex, Lophomyrmex, Lordomyrma, Mayeriella, Meranoplus, Monomorium, Myrmecina, Myrmica, Myrmicaria, Oligomyrmex, Paratopula, Parvimyrma, Pheidole, Pheidologeton, Pristomyrmex, Proatta, Pyramica, Recurvidris, Rhopalomastix, Rhoptromyrmex, Solenopsis, Strumigenys, Temnothorax, Tetramorium, Vollenhovia, Vombisidris. As the first major contribution to the third goal of the program, here we provide: (1) a key to subfamilies, (2) a key to myrmicine genera, and (3) a synopsis of myrmicine and pseudomyrmecine genera known from Vietnam. A second paper will deal with the Aenictinae, Cerapachyinae, Dorylinae, Leptanillinae Amblyoponinae, Ponerinae, Ectatomminae and Proceratiinae, and a third with the Dolichoderinae and Formicinae.